2009
DOI: 10.1128/jvi.01885-08
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatitis C Virus NS4B Protein Can trans -Complement Viral RNA Replication and Modulates Production of Infectious Virus

Abstract: Studies of the hepatitis C virus (HCV) life cycle have been aided by development of in vitro systems that enable replication of viral RNA and production of infectious virus. However, the functions of the individual proteins, especially those engaged in RNA replication, remain poorly understood. It is considered that NS4B, one of the replicase components, creates sites for genome synthesis, which appear as punctate foci at the endoplasmic reticulum (ER) membrane. In this study, a panel of mutations in NS4B was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
145
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(162 citation statements)
references
References 68 publications
14
145
2
1
Order By: Relevance
“…This implication is consistent with an earlier report suggesting that disrupting the amphipathic N-terminal helix of NS4B by site-directed mutagenesis abolished HCV RNA replication in a subgenomic replicon system from HCV genotype 1b ( 9 ). In addition, other studies demonstrated that residues in the C-terminus of HCV NS4B in HCV genotype 2a subgenomic replicon were critical for viral RNA replication ( 10 ). The same group of investigators suggested that the C-terminal domain of NS4B infl uences production of infectious virus.…”
supporting
confidence: 81%
“…This implication is consistent with an earlier report suggesting that disrupting the amphipathic N-terminal helix of NS4B by site-directed mutagenesis abolished HCV RNA replication in a subgenomic replicon system from HCV genotype 1b ( 9 ). In addition, other studies demonstrated that residues in the C-terminus of HCV NS4B in HCV genotype 2a subgenomic replicon were critical for viral RNA replication ( 10 ). The same group of investigators suggested that the C-terminal domain of NS4B infl uences production of infectious virus.…”
supporting
confidence: 81%
“…The hypo-(black arrowhead) and hyperphosphorylated (grey arrowhead) species of NS5A are indicated and actin detection served as a loading control. cells were transfected with siRNAs against each gene and then infected with HCV virions generated by J6-JFH1, a chimeric construct that gives virus titres, which are about 10-fold greater than strain JFH1 (Jones et al, 2009). At 48 h after infection (i.e.…”
Section: Isolation Of Cell Lines Supporting Autonomous Replication Ofmentioning
confidence: 99%
“…In fact most of the Con1-replication enhancing changes within the viral non-structural proteins stimu lated replication at the expense of production of infectious particles. This observation was a first hint suggesting that the non-structural proteins contribute to production of infectious HCV, an observation which was much refined and extended using the infectious JFH1 system (Jones, Murray et al 2007;Steinmann, Penin et al 2007;Yi, Ma et al 2007;Appel, Zayas et al 2008;Ma, Yates et al 2008;Jones, Patel et al 2009;Phan, Beran et al 2009). Besides this, the observation that REMs can interfere with virus production in Con1 genomes provided a simple explanation why the adapted Con1 gen omes unlike the wild type were non-infectious in Chimpanzee or re verted back to the wild type sequence .…”
Section: Cell Culture Infectious Hcv Genomes and Host Cellsmentioning
confidence: 99%